A case report of Sheehan’s syndrome with acute onset, hyponatremiaand severe anemia - Anfuso, S.; Petrelli, T. S.; Soncini, E.; Chiodera, et al., P. (Acta Biomedica Atenei Parmensis, 2009)
Sheehan’s syndrome is a well-known cause of panhypopituitarism secondary to pituitary apoplexy, that generally occurs after an intra- or postpartum bleeding episode characterized by severe hypertension or hemorrhagic shock. The diagnosis can be difficult and is often formulated after some years from the syndrome occurrence. We report the case of a woman with an early diagnosis of early-onset Sheehan’s syndrome associated with severe hyponatremia following dystocic childbirth complicated by postpartum hemorrhage.